Faktor - Faktor Yang Mempengaruhi Kekerasan dalam Rumah Tangga di Jorong Bamban Kenagarian IV Koto Palembayan Kabupaten Agam - Agustiani, Riga; Pasilaputra, Dodi; Afrinaldi, Afrinaldi; Yarni, Linda (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2024)
Domestic violence has a very damaging impact on victims, physically, emotionally and psychologically. Victims often experience trauma, depression, anxiety, and mental health disorders. The purpose of the study was to determine the factors causing domestic violence in Jorong Bamban Kenagarian IV Koto Palembayan focused on economic violence or domestic neglect. This type of research is descriptive qualitative. Data collection techniques through interviews and observations obtained from key informants, namely the wife and supporting informants, namely children, siblings and parents in the field. The data analysis techniques used are data reduction, data presentation, and conclusion drawing.  Based on the results of the research conducted, it can be stated that the factors causing domestic violence in jorong bamban kenagarian IV koto palembayan agam district. The first factor is financial problems, a husband who does not meet the daily needs of the family, the second is jealousy, that the husband has a new family and gets less attention, the third is child problems, lack of affection or attention to children, the fourth is past problems, not accepting the past life of the husband or wife that arises disputes, the fifth is that the husband wants to win alone, always follows the husband's will and the husband only wants to be followed what he wants. Sixth, work, a wife who replaces her husband's position who works to meet household needs, a husband who is stingy towards his own family.